Unique Radio Innovation for the 21st Century Building Scalable and Global RFID Networks - Ranasinghe, Damith C.; Sheng, Quan Z.; Zeadally, Sherali; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
Are you an engineer or a researcher developing RFID systems? Are you a manager considering deploying RFID-based applications? If so, this book is for you. Covering modern RFID systems, the challenges to RFID implementation are addressed using specific industrial research examples and common integration issues. The primary focus is on answering questions surrounding building scalable global Internet-based RFID networks. Key topics include RFID data management, RFID data processing and integration, Real-Time Locating Systems (RTLS) and sensors. The book considers the challenges of and solutions to building and exploiting global networks to guarantee one of the most important business drivers for modern RFID technology: traceability. The authors have drawn together RFID applications from the retail supply chain, asset and product lifecycle management, anti-counterfeiting and cold chain management to explore how global traceability networks can be created using RFID and sensor technologies. They present insights from world$1 (Bs leading research laboratories.s
1. RFID data management -- Database integration -- Speed issues in data movement -- Data stream management -- Efficient data storage and retrieval -- Managing uncertainty -- 2. Global RFID information architectures -- RFID middleware architecture -- RFID and sensor network integration architectures -- RFID data sharing architectures -- Integration with ERP, SCM and MRP -- SOA (Services oriented architecture) -- Enterprise I.T. architecture and middleware touch points -- RFID network management -- COTS and Open Source RFID infrastructure -- Integration of RFID with other applications -- Security -- 3. Internet technologies and RFID: -- Web services and RFID -- RFID and semantic Web -- 4. RFID applications -- (Inventory Management, Asset Management, Retail, Manufacturing, Supply Chain, Pharmaceuticals, Healthcare/Medicine/Biotech/Biology, Aerospace / Airlines / Airport and baggage management, Automotive, Shipbuilding, Entertainment/Media, Financial / Mobile Payments) -- Business versus consumer applications -- Business process redesign and RFID -- Innovative RFID-enabled applications -- RFID case studies and field trials of RFID applications -- Commercial experience with RFID -- Security and access -- 5. Business Issues: -- ROI analysis at unit and enterprise levels -- Revenue models in RFID services -- Effect of RFID on process improvement for the enterprise -- Impact on the CIO/I.T. office -- Legal issues in RFID.
Keywords: Computer science; Computer Communication Networks; Engineering economy; Computer Science; Computer Communication Networks; Engineering Economics, Organization, Logistics, Marketing; Information Systems Applications (incl. Internet).; Production/Logistics/Supply Chain Management